(untitled) (Journal of Philosophy Culture and Political Science, 2015)
In the article the political analysis of concepts such as nationality, ethnicity, nation, ethnic group, diaspora, nationality, as well as the different concepts of ethno-political community and national interests. The importance of national unity in achieving the goals and targets set out in the letter Elbasy NA Nazarbayev «Nurly Jol – way of the future.» Social cohesion and political stability in Kazakhstan is considered as the main factors of development. The paper is also proved by the fact that the conversion of the people of the country into a single ethno-political community and national actions are zologom successful implementation of strategic plans and the protection of national interests.